Writing labor's emancipation : the anarchist life and times of Jay Fox - Hall, Greg, 1961- (University of Washington Press, 2022)
"Jay Fox (1870-1961) was a journalist, intellectual, and labor militant, whose influence rippled across the country. In Writing Labor's Emancipation, historian Greg Hall traces Fox's unorthodox life to shed light on the shifting dynamics in US labor radicalism from the late nineteenth to the early twentieth century. Radicalized as a teenager after witnessing the Haymarket tragedy, Fox embarked on a lifetime of organizing for labor unions, helping build anarchist communities (including Home, Washington), and, perhaps most notably, working as a writer. Thanks to his accessible writing style, insightful working-class perspective, and sharp wit, he became a popular and influential voice, often in dialogue with fellow anarchists such as Emma Goldman and Lucy Parsons. Drawing on previously unused sources, Hall both explores Fox's life and shines a light on the utopians, revolutionaries, and union men and women with whom Fox associated and debated. Hall's research ultimately provides valuable knowledge of the lived experiences of working-class Americans and brings to light alternative visions for activism and social change"-- Provided by publisher.
Keywords: Fox, Jay, -- 1870-1961.; Fox, Jay, -- 1870-1961; Anarchists -- United States -- Biography.; Political activists -- United States -- Biography.; Journalists -- United States -- Biography.; Labor movement -- United States -- History.; Anarchism -- United States -- History.; Anarchistes -- États-Unis -- Biographies.; Activistes -- États-Unis -- Biographies.; Journalistes -- États-Unis -- Biographies.; Mouvement ouvrier -- États-Unis -- Histoire.; Anarchisme -- États-Unis -- Histoire.; HISTORY / United States / State & Local / Pacific Northwest (OR, WA); Anarchism; Anarchists; Journalists; Labor movement; Political activists; United States; Electronic books.; Biographies; History